2017
DOI: 10.33607/bjshs.v3i106.33
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Diet, Physical Activity and Social Factors on Stress Perceived by Students

Abstract: Backgroud. General health status of students is becoming worse due to an intensive lifestyle: a difficult job or study routine, improper diet, and low physical activity (Poteliūnienė, 2010). One of the common problems among students is stress. Stressful situations on a daily basis have been found to be associated with a worse physical and psychological status, harmful habits or personal relationships with friends (Dusselier, Dunn, Wang, Shelley, & Whalen, 2005; Leppink, Odlaug, Lust, Chri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…No association was found between physical activity with depression, anxiety and stress which is supported by the previous studies (28,32,34,35). Conversely, few studies found significant association between physical activity and depression subscale (32,33,34).…”
Section: Discussionmentioning
confidence: 50%
“…No association was found between physical activity with depression, anxiety and stress which is supported by the previous studies (28,32,34,35). Conversely, few studies found significant association between physical activity and depression subscale (32,33,34).…”
Section: Discussionmentioning
confidence: 50%